Correlations Between Soil Exchangeable Ca2+, Mg2+, K+ and Foliar Nutrient Concentrations in Mature Biological Olive Groves (Olea europaea L., cv. 'Chondrolia Chalkidikis'). Issue 4 (21st February 2019) - Chatzistathis, T.; Papaioannou, A.
ABSTRACT: Leaf and soil samples were taken and analyzed from two mature biological olive groves ( Olea europaea L., cv. 'Chondrolia Chalkidikis'), in Thessaloniki, Macedonia, Northern Greece, in order to determine the correlations between soil exchangeable cations and foliar calcium (Ca), magnesium (Mg) and potassium (K) concentrations, and the interrelations among leaf nutrients. Τhe nutritional requirements of trees for both biological groves were exclusively based on patent kali supply and nutrient recycling (via pruning material and weed cut recycling). Foliar K, Ca and Mg were positively correlated with soil exchangeable K, Ca and Mg, in the 40–60 cm layer, then in the 20–40 cm layer. Synergistic uptake mechanisms among Ca 2+, Mg 2+ and K + probably exist. Leaf N was negatively correlated with foliar K, and positively with leaf Ca, Mg and manganese (Mn). Foliar P was negatively correlated with leaf Ca, Mg and Mn, while foliar Ca was positively correlated with leaf Mg and Mn. Foliar Mg was positively related with leaf Mn. High phosphorus (P) may decrease leaf Ca, Mg and Mn. Enhanced Ca may increase leaf Mg and Mn, while high Mg may also enhance foliar Mn. Finally, based on the determination of foliar nutrient concentrations, the nutritional requirements of olive trees in Ca, Mg, K, P, Fe, Zn were sufficiently (or over-sufficiently) satisfied. However, additional organic fertilization is needed, in order to achieve optimum levels of N, B and Mn (since their foliar concentrations were slightly insufficient). The correlations between leaf and soil exchangeable Ca, Mg and K, as well as among foliar nutrients should be taken into consideration, in order to achieve successful organic fertilization for mature biological olive groves, and to avoid nutritional imbalances and disorders.